If (x+5) is a factor the equation will equal zero when x=-5 so
3(-5^2)+14(-5)+k=0
75-70+k=0
5+k=0
k=-5
Answer:
Step-by-step explanation:
Let Freda's sum = x
Donnie has 3/4 x
He spends 63 dollars. His sum is now
3/4x - 63
Now the equation looks like this
6(3/4x - 63) = x Remove the brackets
6*3/4 x - 378 =x
6 * 3/4 = 4 1/2
4 1/2 x - 378 = x Add 378 to both sides
4 1/2 x = x + 378 Subtract x from both sides
3.5 x = 378 Divide by 3.5
x = 378 /3.5
x = 108
Since x = 108, that's how much Freda had. (She spent nothing).
Answer: answer is 8 because -5 + 1 = -4 then + 10 = 4
The equation was just flipped around, it will equal the same no matter what.
I hope this helps!! :)
The parent function that is f(x) = log(x) is transformed firstly, to log(x+2)
since, we can see after that we can directly convert it to log(2x+4)
and after one reflection it will become log(-2x-4)
°ω° Hope this helps :)
Good luck bud :D